Obstructive Jaundice Due to Bile Duct Tumor - Lydia D Simatupang; Laurentius Lesmana; Feriadi Suwarna; Ari Fahrial Syam (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2004)
We reported here a rare case of a 62 year old male patient with obstructive jaundice due to bile duct tumor. The main clinical features were yellowish eye and skin, followed by pruritus and clay-colored stool. Ultrasonography showed common bile duct dilatation and without evidence of stones. Computed Tomography Scan of upper abdomen showed a mass which were thought of head of pancreas origin. Endoscopic Retrograde Cholangio Pancreatograph revealed tight narrowing of the distal bile duct to a malignant tumor. A stent was inserted to allow biliary drainage. A surgical plan for billio digestive anastomosis was rejected by the patient and family. Keywords: bile duct tumor, CT scan abdomen, ERCP